THE FIRST RESULTS OF THE KEYNESIAN PROGRAM OF REVITALIZATION OF THE JAPANESE ECONOMY - U. T. Dzhamakeev (Модернизация, инновация, развитие, 2015)
In this paper we present an application of Tobin's dynamic monetary model to the analysis of depressed economy during the crisis. The example of the stagnant Japanese economy shows that a strong Keynesian program revival adopted by the government of Prime Minister Shinzo Abe in 2012, brings the first positive results: the movement of the state of chronic deflation, the revival of the economy and significant economic growth.